2022
DOI: 10.1177/14614448211059114
|View full text |Cite
|
Sign up to set email alerts
|

For better and for worse: A panel survey of how mobile-only and hybrid Internet use affects digital skills over time

Abstract: Public policies across the world are tackling Internet access inequality through mobile connections, which has led to an increase in mobile-only use. However, digital skills remain as a stumbling block to achieve digital inclusion. Using a two-wave panel survey on a representative sample conducted in Chile between 2018 and 2020, this study investigates how different mode of access (i.e. mobile-only vs mobile and computer) affects digital abilities over time. Results show significant differences in skills by mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 70 publications
(136 reference statements)
1
7
1
Order By: Relevance
“…Conceptualizations of digital skills have established their relevance for usage, as well as for social inclusion as a consequence of usage (Hargittai & Micheli, 2019;Helsper, 2021;Reisdorf & Groselj, 2018;van Dijk, 2020). This claim has been empirically supported by a recent panel study on internet use and digital skills (Correa et al, 2022). The relationship between digital skills, internet usage, and the feeling of inclusion in the information society is especially relevant in a society where the digital is the norm (Allmann & Blank, 2021).…”
Section: Associations With Digital Skillsmentioning
confidence: 84%
See 1 more Smart Citation
“…Conceptualizations of digital skills have established their relevance for usage, as well as for social inclusion as a consequence of usage (Hargittai & Micheli, 2019;Helsper, 2021;Reisdorf & Groselj, 2018;van Dijk, 2020). This claim has been empirically supported by a recent panel study on internet use and digital skills (Correa et al, 2022). The relationship between digital skills, internet usage, and the feeling of inclusion in the information society is especially relevant in a society where the digital is the norm (Allmann & Blank, 2021).…”
Section: Associations With Digital Skillsmentioning
confidence: 84%
“…Theoretical approaches like the digital divide framework or the digital inequalities perspective have argued that a person's digital skills are impacted by their social position (van Dijk, 2020), which has been evidenced empirically as well (see e.g., Bonfadelli, 2002;Büchi et al, 2016;Ragnedda, 2020). Differences in digital skills can lead to a variety of internet uses and also to various consequences such as different levels of inclusion in the information society (Correa et al, 2022). This makes the study of digital skills highly relevant, especially in societies where the digital is increasingly becoming the norm and both private corporations, and governments employ a digital-first strategy (Allmann & Blank, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research (Cabello et al, 2021; Chen & Li, 2021) has found that those who rely on one device have fewer digital abilities and a narrower set of digital media use skills compared with those who access the Internet through multiple devices. Furthermore, changing mode of access has an effect on digital skills over time (Correa et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…These apprehensions are linked to mainly two key dimensions: digital skills and range of online activities. Studies have consistently found that multidevice access is related to higher skills compared with mobile‐only access (Cabello et al, 2021; Chen & Li, 2021; Correa et al, 2022; van Deursen & van Dijk, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation